Primate Cytogenetics and Comparative Genomics - Sineo, Luca; Stanyon, Roscoe (Atti, 2006)
This volume is a collection of contributions of a Florentine post congress symposium on "Primate Cytogenetics and Comparative Genomics" held on occasion of the XX International Primatological Congress (Turin in 2004). Comparative Molecular Cytogenetics and Genomics are two rapidly expanding fields. Researchers from Italy, Germany, Spain, United States and Japan meet in Florence to discuss over a two day period recent advances and summarize the current state of the science.